Alanine aminotransferase levels as therapeutic targets after nucleotide/nucleoside analog therapy in patient with chronic hepatitis B. Issue 1 (4th October 2022) - Kirino, Sakura; Tamaki, Nobuharu; Kurosaki, Masayuki; Kaneko, Shun; Inada, Kento; Tanaka, Yuki; Ishido, Shun; Yamashita, Koji; Nobusawa, Tsubasa; Matsumoto, Hiroaki; Hayakawa, Yuka; Kakegawa, Tatsuya; et al.
Abstract: Aim: Alanine aminotransferase (ALT) is a criterion for the introduction of nucleotide/nucleoside analog (NA), and ALT levels are decreased by NA treatment. However, the association between post‐treatment ALT levels and hepatocellular carcinoma (HCC) risk remains unclear. To fill this gap, we aimed to establish a target value of ALT level during NA treatment. Methods: In total, 413 patients with chronic hepatitis B who received entecavir, tenofovir alafenamide, or tenofovir disoproxil fumarate were enrolled. The subsequent development of HCC was examined and a target value of ALT level during NA treatment as a risk marker for HCC was evaluated. Results: The median follow‐up duration was 5.1 years, during which time 27 patients (8.6%) developed HCC. ALT level at the start of treatment was not associated with HCC development ( p = 0.08). When stratified by ALT at 1 year after NA initiation, the cumulative 3‐ and 5‐year rates of HCC for patients with ALT ≥21 IU/L were 11.5% and 18.1%, and those with ALT <21 IU/L was 2.3% and 6.5%, respectively. Patients with ALT <21 IU/L had a significantly lower risk of HCC development compared with patients with ALT ≥21 IU/L ( p = 0.002). In multivariable analysis adjusting age, sex, and platelet counts, ALT ≥21 IU/L was an independent risk factor of HCC development with hazard ratio of 4.5 (95% confidence interval: 1.01–20.4). Conclusions: ALT <21 IU/L at 1 year after NA initiation has a lower risk of HCC and could be used as a target value for NA treatment.